The Characteristics of Urease Enzyme of Green Bean Seeds (Vigna radiata L.) and Its Activity as An Antifungal Against Candida albicans - Niken Istikhari Muslihah; Zusfahair Zusfahair; Dian Riana Ningsih; Fajar Nuradha (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Urease is an enzyme responsible for catalyzing the hydrolysis reaction of urea into CO2 and NH3. The urease isolated in this study came from green bean seeds. The urease enzyme was then tested for its antifungal activity against Candida albicans. The research aims to extract and characterize the urease enzyme from green bean seeds and explore its potential use as an antifungal agent. Green bean seeds were smoothed with a mortar and pestle, followed by homogenization using a stirrer and cold centrifugation. The crude extract of the urease enzyme was assessed for its activity through the Nessler method and measured by employing a UV-Vis spectrophotometer at a wavelength of 500 nm. The well-diffusion method was conducted to determine the antifungal activity of rough enzyme extracts against C. albicans. Positive controls were 100% ketoconazole, and negative controls used a pH buffer of 7. The characterization of the urease enzyme from green bean seeds revealed the optimum urease activity at a concentration of 0.25 M, pH level of 7, and an incubation temperature of 35°C with a value of 32.115 U/mL. Maximum reaction rate (Vmax) and Michaelis-Menten constant value (KM) were obtained at 56.497 U/mL and 0.215 M, respectively. Antifungal tests of C. albicans resulted in strong inhibitory activity at a concentration of 100% crude urease extract of 12 mm inhibition zone. The inhibitory concentration value grows at least 0.5% by 0.25 mm and positive control of 19.802 mm.